Forward and Back: Motifs of Inhibition in Olfactory Processing - Bazhenov, Maxim (Neuron, 2010)
The remarkable performance of the olfactory system in classifying and categorizing the complex olfactory environment is built upon several basic neural circuit motifs. These include forms of inhibition that may play comparable roles in widely divergent species. In this issue of Neuron, a new study by Stokes and Isaacson sheds light on how elementary types of inhibition dynamically interact.